PHYTOCHEMICAL ANALYSIS AND ANTIBACTERIAL ACTIVITIES OF GUNDELIA TOURNEFORTII AND MALVA SYLVESTRIS LEAF EXTRACTS IN KURDISTAN IRAQ - Jalal, Mustafa J. (Journal of Medical Genetics and Clinical Biology, 2024)
This study aims to evaluate the phytochemical composition and antibacterial activities of Gundelia tournefortii and Malva sylvestris leaf extracts from the Kurdistan region of Iraq. Phytochemical screening was performed to identify the presence of key compounds, while the antibacterial activity was assessed against various bacterial strains. The results indicated significant phytochemical constituents and promising antibacterial properties, suggesting potential uses in traditional and modern medicine.